Particulate matter (PM) oxidative potential: Measurement methods and links to PM physicochemical characteristics and health effects. Issue 2 (17th January 2023) - He, Linchen; Zhang, Junfeng (Jim)
Abstract: It has been widely accepted that the induction of reactive oxygen species (ROS) is an important pathophysiologic pathway linking particulate matter (PM) exposure and adverse health effects. ROS can be either present on and/or within PM or generated in vivo by the interactions between PM and biological systems. Within the context of toxicology, PM oxidative potential (OP) is the capacity of PM to oxidize molecules in biological tissues or cells directly by oxidants that are present on and/or within PM and indirectly by the ROS generated via PM interactions with the biological system (e.g., fluids, cells, and tissues). In this review, we summarized the current PM OP measurement methods, current understanding of how PM physical characteristics and chemical compositions affect OP, and the epidemiological and toxicological evidence on whether PM OP is a better indicator than PM mass concentration for health effects. Among the two major types of OP measurement methods, cellular assays have been regarded to better reflect the actions of PM in a biological system than acellular assays. Recent epidemiological studies have associated short-term PM OP exposure with adverse cardiorespiratory health outcomes. Little is known about the health effects of long-term PM OP exposure and on the effect beyond the cardiovascular and respiratory systems. The existing evidence may be sufficient to suggest the use of PM OP as a more health-relevant exposure metric than conventional PM mass concentration, but critical methodologic issues must be resolved before this metric can be widely and accurately used. Graphical abstract: UF0001